Koncepcja i metody oceny różnorodności biologicznej lasów Europy - Kornatowska, Bożena (Leśne Prace Badawcze, 2012)
One of the main paradigms in present-day ecology and environmental policy is the concept of biodiversity. A review is presented of biodiversity evaluation methods illustrated with an example from European forests. The adoption of a common definition of biodiversity and adequate methodology during data collating are important points of reference in biodiversity appraisals. There is a necessity to build a scientifically sound and consistent system of indicators for biodiversity evaluation in forests.